Identify determinant of contraceptive use in rural set up of Surat district, Gujarat - Solanki, Rajendra; Patel, Hiteshri C.; Kosambiya, J. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: In spite of significant growth and expansion of family planning programme, pregnancy continues to be unplanned. This study has been conducted to identify determinant responsible for use of contraception. The aim of the study was to determine the factors affecting the use of the contraceptives. The objectives were to study Socio – demographic, fertility profile of eligible couples and its relation to use of contraception Methods: This is a cross sectional study conducted during period of 20th September 2014 to 15th January 2015. Three PHCs were selected purposively from Olpad taluka of the Surat District. Two Sub Centers were selected randomly from each PHC. Data regarding eligible couples were collected from Sub Center register. From each Sub Center, 47 eligible women were selected randomly. Total sample size was 280 (CPR: 60%, DLHS-3). Results: Mean age of study participants were 29.14±6.7 years. Out of total women, 18.6% women were married before attaining the age of 18 years. More than 50% women were 20-24 years of age group at the time of birth of first child where as 25.4% women gave birth to first child before the age of 20 years. There was significant association between use of Contraceptive methods with factors like age of women, caste, religion, education of women, education of husband and number of children (p<0.05). At the time of sterilization, number of children and gender of last child plaed a significant role. Conclusions: Women should be empowered with education regarding use of contraception. Child marriage act should be strictly followed.